STUDI PUTUSAN KASUS ANGGOTA POLRI PELAKU PENELANTARAN ANAK DALAM RUMAH TANGGA - ASHADY, SUHEFLIHUSNAINI; DUDY, ARYADI ALMAU (Universitas Mahasaraswati K. Mataram, 2024)
This research was conducted to examine the accountability of a member of the Indonesian National Police who neglected a child in the household based on the Kupang district court decision Number 53/Pid.Sus/2019/PN. Kpg. In this case, there was a dissenting opinion from the judge who decided the case. This research is normative legal research so the approaches used are the statutory approach, conceptual approach and case approach. The results of the research show that the judge in his decision used law number 23 of 2004 concerning the elimination of domestic violence to judge child neglect committed by the perpetrator. The judge also continued to consider the perpetrator's profession as an aggravating element. Apart from that, judges not only prioritize aspects of legal certainty, but also aspects of justice and legal benefits. The judge handed down a lower sentence than the prosecutor's request because the judge during the trial discovered the fact that the victim also contributed to the mistake so that the victim and her child were abandoned by the perpetrator. In this case, the victim left the perpetrator's residence, even though he was not divorced